Results in the Latin America and Caribbean Region 2018, Volume 12 - World Bank (World Bank, Washington, DC, 2022)
The Latin America and the Caribbean region is growing again after a number of difficult years. However, the recovery is fragile and the prospects for 2018 are falling short of initial expectations due to challenges faced by some of the countries in our region, particularly in South America. These challenges highlight the need to focus on supporting faster and more equitable growth to make sure that the profound social transformation the region experienced during the first decade of the century is protected and expanded. During that time, the commodity boom fueled strong and widespread growth, cutting poverty rates in half. However, the pace of poverty reduction and growth of the middle class has stalled since then. Fortunately, the gains have not been reversed, but many people remain vulnerable to slipping back into poverty.